Communal Awareness of Diversity to Enforce Tolerance Tourism in Singkawang City - SETYOWATI, Dewi Liesnoor; ASTUTI, Tri Marhaeni Puji; KURNIAWAN, Edi (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
Indonesia is a large country that consists of various ethnicities, races, religions, social classes, and cultures, vulnerable to conflicts. It's necessary to maintaining the unity amid the diversity or ‘Kebhinekaan’. The objectives of the research to: 1) explore the characteristics of diversity; 2) analyze communal awareness through the activities of tolerance tourism; and 3) analyze the values of diversity in supporting the concept of tolerance tourism. Qualitative methods are used in this study. Researchers used participatory observation and document study technique to collect the data from relevant archives and documents, to interviews with relevant parties to explore the characteristics of ethnicities, cultures, and tolerance tourism. The study revealed a number of facts, including: a) the characteristics of diversity among the people in Singkawang City that have a distinctive paradigm in assessing diversity that actually originates from the wisdom of Malay, Chinese, Dayak culture, and other nations that have lived in the city; b) a high communal awareness in the activities of tolerance tourism to promote the sense of caring among ethnicities; and c) the diversity of multiethnic communities in supporting tolerance tourism by promoting the values of tolerance, mutual respect, and solidarity.